Isolation and identification of a high molecular weight protein in sow milk. (16th January 2015) - Qin, Y.; Qi, N.; Tang, Y.; He, J.; Li, X.; Gu, F.; Zou, S.
Abstract : A high molecular weight protein (HMWP) was isolated and purified from sow milk, and some of its biochemical characteristics and biological functions were identified. The origin of HMWP was also investigated. The molecular weight of HMWP was determined to be about 115 000 and 114 800 by SDS-PAGE and gel filtration, respectively. The sequence of 10 amino acids in N-terminal of HMWP was Ala-Leu-Val-Gln-Ser-Cys-Leu-Asn-Leu-Val. The sequence was blasted against GenBank. No protein showed significant similarity with this sequence suggesting the HMWP may be novel. The result of liquid chromatography mass spectrometry (LC-MS) also proved HMWP could be a novel protein. By amino acid assay, HMWP was rich in glutamate (including glutamine), cysteine, glycine, aspartic acid (including asparagines) and proline. The content of hydrophobic amino acids (Ala, Val, Leu, Ile, Met, Phe and Pro) was lower at 18.59% of the total amino acids suggesting HMWP has high solubility in water. Western blots of lectins were used to identify the kinds of carbohydrate residues attached to HMWP qualitatively. The result showed that HMWP was a kind of glycoprotein containing N -acetylneuraminic acid (NeuNAc), mannose (Man) and/or N -acetylglucosamine (GlcNAc). By isoelectric focusing, HMWP pI was found to be 5.1. Compared with milk fat globule membrane protein (MFGMP) isolated from the sow milk in SDS-PAGE, MFGMP did not contain HMWP. HMWP was assumed to be a secretory milk protein. HMWP was not found in bovine, goat, rabbit or human milk in SDS-PAGE gel suggesting HMWP may be unique to sow milk. By Western blot, HMWP could be detected in sow milk, not in sow serum, which suggests it is synthesized and secreted by the mammary gland. HMWP concentrations in sows milk were the lowest in the first day of lactation, rose significantly during lactation 1 to 7 days. The HMWP content of sows milk remained relatively constant ((1.95±0.13) g/l) during lactation 7 to 20 days. HMWP significantly inhibited Escherichia coli in a dose related manner in vitro . Overall, HMWP could be a novel sow milk protein with implications for the mammary gland and the piglet.